Immunity to retroviral infection: The Friend virus model - Hasenkrug, Kim J. (National Academy of Sciences, 1997)
Friend virus infection of adult immunocompetent mice is a well established model for studying genetic resistance to infection by an immunosuppressive retrovirus. This paper reviews both the genetics of immune resistance and the types of immune responses required for recovery from infection. Specific major histocompatibility complex (MHC) class I and II alleles are necessary for recovery, as is a non-MHC gene, Rfv-3, which controls virus-specific antibody responses. In concordance with these genetic requirements are immunological requirements for cytotoxic T lymphocyte, T helper, and antibody responses, each of which provides essential nonoverlapping functions. The complexity of responses necessary for recovery from Friend virus infection has implications for both immunotherapies and vaccines. For example, it is shown that successful passive antibody therapy is dependent on MHC type because of the requirement for T cell responses. For vaccines, successful immunization requires priming of both T cell and B cell responses. In vivo depletion experiments demonstrate different requirements for CD8(+) T cells depending on the vaccine used. The implications of these studies for human retroviral diseases are discussed.